Maria Relaki and Yiannis Papadatos (eds) From the Foundations to the Legacy of Minoan Archaeology. pp. 331, 69 b/w ills, 9 tables. 2018. Oxford: Oxbow Books (Sheffield Studies in Aegean Archaeology). ISBN 978-1-78570-926-5, paperback £38. - Dickinson, Oliver (Journal of Greek Archaeology, 2020)
This volume contains final versions of the majority of papers given at the 14th Sheffield Round Table in Aegean Archaeology, 29-31 January 2010, so it has taken a long time to arrive, but it can be said straight away that specialists in Minoan archaeology should find it worth the wait. The Round Table was held to honour Keith Branigan, founder of the Sheffield Centre for Aegean Archaeology, and its topics were evidently chosen to reflect the areas in which he has made particularly significant contributions. Thus, the papers published here are concerned principally with different aspects of the rich field of funerary activity, especially in the Prepalatial period, but also with patterns of settlement and land exploitation, and with the processes of development that brought the Minoan civilisation into being. The contribution by Relaki, the co-editor (Ch. 2), stands out in focusing on another field in which Branigan was active at an early stage, that of developments in technology, their spread within Crete, and their links with the outside world, notably the Cyclades and Egypt.